JARINGAN KOMUNIKASI, MODAL SOSIAL DAN ENERGI SOSIAL BUDAYA KREATIF DALAM MENGEMBANGKAN KELEMBAGAAN PETERNAKAN, SEBUAH TINJAUAN TEORITIS - Muh. Zainal S. (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
Efforts  to  build  cooperation  that  is  born  from  local  wisdom  values  of  a  society  that  aims  to  overcome  the problems  for  example  in  the  aspect  of  livestock  business  activity  is  a  component  of  social  capital  and  social energy  that  must  be  developed  and  maintained  in  order  to  achieve  empowerment  and  independence.  These efforts require communication networks both within and outside the group. Through the communication network occurs the process of communication to share messages or information, especially related to livestock farming. Communication  networks,  social  capital  and  social  energy  of  creative  culture  have  an  important  role  in developing  a  community  institution  that  is  expected  to  lead  to  the  realization  of  empowerment  and independence.  This  article  aims  to  produce  the  theoretical  descriptions  of  communication  networks,  social capital,  institutions,  and  creative  social  and  cultural  energies.  The  method  of  writing  this  article  using  a qualitative approach using literature study (desk study) is by collecting relevant literature.  Keywords: communication network, energy of creative cultural social, social capital